A comparative study to evaluate the effects of intranasal steroid spray, isotonic saline nasal irrigation and combination therapy in patients with allergic rhinitis - Gangaraju, Smitha Soubhagya; Pillai, Nikitha; Manthal, Vijaylaxmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Allergic rhinitis (AR) is characterized by inflammatory changes in the nasal mucosa caused by exposure to inhaled allergens. AR clinically having 2 or more symptoms of anterior or posterior rhinorrhea, sneezing, nasal blockage or itching of the nose during two or more consecutive days for more than 1 hour on most days which are caused by allergen exposure leading to an IgE mediated reaction. Nasal steroids and antihistamines are considered as gold standard treatment of choice in moderate to severe AR. This study was taken to evaluate the efficacy of intranasal steroid spray, isotonic saline nasal irrigation, combination therapy and to compare all 3 treatment modalities. Methods: 75 patients of AR who met inclusion criteria were sequentially divided into 3 groups. Group A was intranasal steroid spray, group B was isotonic saline nasal irrigation, group C was combination of both intranasal steroid spray and saline nasal irrigation. Total nasal symptoms score was compared before and after 1 month of treatment. Results: Mean total nasal symptoms score before treatment in groups A, B and C was found to be 13.72, 12.96 and 13.68 respectively and after 1 month of treatment total nasal symptoms score was seen 8.28, 8.76 and 3.72 respectively. Conclusions: The combined use of saline nasal irrigation along with intranasal corticosteroids is found to be more effective in reducing the symptoms of patients with allergic rhinitis when compared to individual therapies.